Roles of Co-solvents in hydrothermal liquefaction of low-lipid, high-protein algae. (August 2020) - Cui, Zheng; Cheng, Feng; Jarvis, Jacqueline M.; Brewer, Catherine E.; Jena, Umakanta
Highlights: Alcohols help transfer protein fragments from the aqueous phase to bio-crude oil. Ethanol, isopropanol and glycerol accelerate Maillard reactions. Crude glycerol improves bio-crude oil yield and energy recovery from low-lipid algae. Abstract: Valorization of algal biomass is often limited by its low lipid content. Here, different alcohols: ethanol, isopropanol, and glycerol, were studied as co-solvents to improve the conversion efficiency of a lipid-poor microalgae, Galdieria sulphuraria, by hydrothermal liquefaction. Bio-crude oil yield increases, from 13 to 73 wt% (on dry algae basis), were attributed to the alcohols facilitating the transfer of algal protein-derived fragments from the aqueous phase into the oil phase. A series of characterization results showed that bio-crude oil formation was mainly the result of alcohols reacting with algal fragments via Maillard reactions, alkylation, and esterification, respectively. Insights into the synergistic effect of low-lipid feed and alcohol provide mechanistic support for choosing an alcohol-rich waste, crude glycerol, to improve bio-crude oil production from HTL of wastewater-grown G. sulphuraria . Promising improvements in yield and energy recovery indicates competitive economics for a low-lipid biomass waste-to-biofuel conversion technique.